Nectin-4 Expression Is an Independent Prognostic Biomarker and Associated With Better Survival in Triple-Negative Breast Cancer - Zeindler, Jasmin; Soysal, Savas Deniz; Piscuoglio, Salvatore; Ng, Charlotte K. Y.; Mechera, Robert; Isaak, Andrej; Weber, Walter Paul; Muenst, Simone; Kurzeder, Christian (Frontiers in Medicine, 2019)
Background: Triple-negative breast cancer (TNBC) represents about 10-20% of all invasive breast cancers and is associated with a poor prognosis. The nectin cell adhesion protein 4 (Nectin-4) is a junction protein involved in the formation and maintenance of cell junctions. Nectin-4 has previously shown to be expressed in about 60% of TNBC as well as in TNBC metastases, but to be absent in normal breast tissue, which makes it a potential specific target for TNBC therapy. Previous studies have shown an association of Nectin-4 protein expression with worse prognosis in TNBC in a small patient cohort. The aim of our study was to explore the role of Nectin-4 in TNBC and confirm its impact on survival in a larger TNBC patient cohort. Material and Methods: We performed immunohistochemical staining for Nectin-4 on a tissue microarray encompassing 148 TNBC cases with detailed clinical annotation and outcomes data. Results: A high expression of Nectin-4 was present in 86 (58%) of the 148 TNBC cases. In multivariate survival analysis, high expression of Nectin-4 was associated with a significantly better overall survival when compared with low expression of Nectin-4 (p<0.001). Nectin-4-high expression has been significantly associated with a lower tumor stage (p = 0.025) and pN0 lymph node stage (p = 0.034). Conclusion: Our results confirm that expression of Nectin-4 serves as a potential prognostic marker in TNBC and is associated with a significantly better overall survival. In addition, Nectin-4 thus represents a potential target in TNBC, and its role in molecular defined breast cancer subtype should be investigated in larger patient cohorts.